2016
DOI: 10.1111/bjd.14888
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictors of a high clinical response in patients with psoriasis on biological therapy in daily practice: results from the prospective, multicenter BioCAPTURE cohort

Abstract: A limited number of patients achieved PASI 100 or PASI 90 at 24 weeks of biological treatment. Including an absolute PASI score in the assessment of psoriasis severity is important. Baseline BMI was an important, modifiable predictor for a high response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 31 publications
3
46
0
1
Order By: Relevance
“…Similarly to the results of our study, baseline obesity was not found to be associated with infliximab's response attainment rates in the retrospective study conducted in Spain . Yet, several other studies have reported high BMI to be a negative predictor of response to biologics (including infliximab) . Interestingly, while an association of BMI with drug survival to biologics (a commonly used indicator of treatment effectiveness) in moderate‐to‐severe plaque psoriasis patients has been identified in the retrospective ORBIT study, and in the BIOBADADERM Registry, it should be noted that in another study identifying BMI to be a predictor of drug survival, this factor was not found to be associated with clinical response, cautioning against universal extrapolation of predictors of drug survival to predictors of clinical response.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly to the results of our study, baseline obesity was not found to be associated with infliximab's response attainment rates in the retrospective study conducted in Spain . Yet, several other studies have reported high BMI to be a negative predictor of response to biologics (including infliximab) . Interestingly, while an association of BMI with drug survival to biologics (a commonly used indicator of treatment effectiveness) in moderate‐to‐severe plaque psoriasis patients has been identified in the retrospective ORBIT study, and in the BIOBADADERM Registry, it should be noted that in another study identifying BMI to be a predictor of drug survival, this factor was not found to be associated with clinical response, cautioning against universal extrapolation of predictors of drug survival to predictors of clinical response.…”
Section: Discussionsupporting
confidence: 84%
“…Further, most cases of psoriasis in IBD patients under anti-TNF therapy are considered paradoxical reactions for the fact that anti-TNF biologics have shown efficacy in non-IBD patients with psoriasis 8. In line with this assertion, Guerra et al7 found 125 psoriasis cases from a total of 7,415 patients treated with TNFα inhibitors for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this assertion, Guerra et al7 found 125 psoriasis cases from a total of 7,415 patients treated with TNFα inhibitors for IBD. In fact, all of the TNFα inhibitors available on the market are reported to have the potential to cause psoriasis-like adverse cutaneous side effects 5,8. Therefore, topical treatment without discontinuing the biologic is given priority over withdrawing the biologic in IBD cases, which become complicated by psoriasis, unless the cutaneous lesions are severe enough to impair patient’s quality of life seriously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice the patient population is typically heterogeneous, older, has more comorbidities, and may be less adherent to lifestyle and treatment recommendations than patients included in RCTs. Few studies have investigated what factors predict treatment response of biologics in psoriasis in clinical practice . Yet, characteristics predicting a high response could be useful for physicians trying to individualize and optimize treatment.…”
mentioning
confidence: 99%